Treatment Failure in Femoral Neck Fractures in Adults Less Than 50 Years of Age: Analysis of 492 Patients Repaired at 26 North American Trauma Centers. Issue 6 (June 2022) - Collinge, Cory A.; Finlay, Andrea; Rodriguez-Buitrago, Andres; Beltran, Michael J.; Mitchell, Phillip M.; Mir, Hassan R.; Gardner, Michael J.; Archdeacon, Michael T.; Tornetta, Paul
Abstract : Objectives: To assess the operative results of femoral neck fractures (FNFs) in young adults in a large multicenter series, specifically focusing on risk factors for treatment failure. Design: Large multicenter retrospective cohort series. Setting: Twenty-six North American Level 1 trauma centers. Patients: Skeletally mature patients younger than 50 years with displaced and nondisplaced FNFs treated between 2005 and 2017. Intervention: Operative repair of FNF. Main outcome measurements: The main outcome measure is treatment failure: nonunion and/or failed fixation, osteonecrosis, malunion, and need for subsequent major reconstructive surgery (arthroplasty or proximal femoral osteotomy). Logistic regression models were conducted to examine factors associated with treatment failure. Results: Of 492 patients with FNFs studied, a major complication and/or subsequent major reconstructive surgery occurred in 45% (52% of 377 displaced fractures and 21% of 115 nondisplaced fractures). Overall, 23% of patients had nonunion/failure of fixation, 12% osteonecrosis type 2b or worse, 15% malunion (>10 mm), and 32% required major reconstructive surgery. Odds of failure were increased with fair-to-poor reduction [odds ratio (OR) = 5.29, 95% confidence interval (CI) = 2.41–13.31], chronic alcohol misuse (OR = 3.08, 95% CI = 1.59–6.38), comminution (OR = 2.63, 95% CI = 1.69–4.13), multiple screw constructs (vs. fixed-angle devices, OR = 1.95, 95% CI = 1.30–2.95), metabolic bone disease (OR = 1.77, 95% CI = 1.17–2.67), and increasing age (OR = 1.03, 95% CI = 1.01–1.06). Women (OR = 0.57, 95% CI = 0.37–0.88), Pauwels angle ≤50 degrees (type 1 or 2; OR = 0.64, 95% CI = 0.41–0.98), or associated femoral shaft fracture (OR = 0.19, 95% CI = 0.10–0.33) had lower odds of failure. Conclusions: FNFs in adults <50 years old remain a difficult clinical and surgical problem, with 45% of patients experiencing major complications and 32% undergoing subsequent major reconstructive surgery. Risk factors for complications after treatment of displaced FNFs were numerous. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.